PERCUKAIAN TANAH MENURUT PERSPEKTIF ISLAM - Awang Othman, Mahmud Saedon (Jurnal Syariah, 2019)
The article at glance attemps to survey the position of taxation of land (al-kharaj) accordillg to Islamic perspective. In other words, it tries to view Islamic rulillgs (hukm) concernillg land’s tax, its procedures as well as its measurements. As far as the above matter is concerned, it is hopefully will assist ill order to implement the taxation of land in accordance to the spirit of Islam.